The power‐of‐pull of economic sectors: A complex network analysis. Issue 5 (11th April 2013) - Luo, Jianxi
<x xml:space="preserve">Abstract</x> To compare the relative power of individual sectors to pull the entire economy, i.e., the power‐of‐pull, this article utilizes a complex system perspective to model the economy as a network of economic sectors connected by trade flows. A sector's power‐of‐pull is defined and calculated as a function of the powers‐of‐pull of those sectors that it pulls through network linkages, and their powers‐of‐pull are, in turn, functions of those sectors that they further pull ad infinitum throughout the network. Theoretically, boosting activities in sectors with a higher power‐of‐pull will generate greater network effects while stimulating the entire economy, especially during recessions. This method is applied to the United States in the years before and after the 2008 financial crisis. The results provide a fresh look at the U.S. government's economic revival policies and reveal fundamental changes in the economic structure of the U.S. This work advocates a network‐based analysis of the economy as a complex system. © 2013 Wiley Periodicals, Inc. Complexity 18: 37–47, 2013